A study on barriers of innovation in warehouses and distribution centers - Yu, Yang. (2013)
With logistics receiving more attention from the entire industry, a lean and efficient supply chain becomes the new hot topic in logistics industry. As a consequence, competition between supply chains becomes fiercer. As an important link and node in the supply chain, warehouses and distribution centers have to upgrade themselves to survive in the evolution of logistics industry. One way for them to succeed is to innovate.